Glasbena matica Maribor - Potočnik, Dragan (Studia Historica Slovenica, 2001)
The Musical centre (Glasbena matica) was the major Slovene institution of music in Maribor in the period between the World Wars. It was established in 1919. With the support of conscientious Maribor inhabitants, the Musical centre between the two Wars promoted Slovene music in the city. Under the guidance of musicians and composers the first mixed choir of the Maribor Music Centre was among the best Slovene choirs. At the invitation of the Music Centre, Czech, Bulgarian, Serb and Swiss choirs came to Maribor. The school of the Music Centre prepared future musicians and singers, as well as educating the concert attending public
Keywords: choires; cultural history; društva; glasbena društva; glasbena šola; institutions of music; kulturna društva; kulturna zgodovina; Maribor; music schools; musical centres; orchestras; orkestri; pevski zbori